Pembelajaran Bahasa Arab Berbasis Budaya Lokal Bima untuk Meningkatkan Penguasaan Mufradat Siswa Kelas X MA Al-Husaini Kota Bima - Aldin Aldin; Muslimin Muslimin; Sri Wahyuningsih (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This research was motivated by the low mastery of Arabic vocabulary among tenth-grade students at MA Al-Husaini, Bima City, due to the learning process being conventional, textual, and lacking relevance to the students' socio-cultural environment. The purpose of this study was to improve vocabulary mastery through the implementation of learning strategies based on Bima local culture. The method used was Classroom Action Research (CAR), implemented in two cycles. The study subjects consisted of 27 tenth-grade students. Data collection techniques included tests (pre-test and post-test), observation, and documentation. The results showed a significant increase in students' vocabulary mastery. In Cycle I, the average class score reached 74.6, with a completion rate of 70.4%. After improvements in Cycle II, which included strengthening the use of Arabic-Bima loan terms and using more varied visual media, the average class score jumped to 80.0, with a completion rate of 100%. Qualitatively, the integration of local culture can increase students' enthusiasm and confidence in pronouncing vocabulary due to an emotional connection to the material being taught. This study concludes that local wisdom-based learning is effective in bridging students' understanding and facilitating the natural internalization of Arabic vocabulary.